Rethinking the representation of Gustavus Adolphus: the case of William Watts and The Swedish Intelligencer, 1630–33. Issue 4 (8th August 2019) - Turnbull, Emma C.
ABSTRACT: Between 1630 and 1633, English newsbooks resounded with tales of King Gustavus Adolphus of Sweden's victories against the "popish" armies of Emperor Ferdinand II. Such literary praise has been widely associated with Calvinist disapprobation of Charles I's pacific foreign policy. This article throws new light on the alternative, non-Calvinist sources of enthusiasm for Gustavus Adolphus in the newsbook, The Swedish Intelligencer, which portrayed the Swedish king as the figurehead of a broad, confessionally flexible, pan-Protestant cause. This has important implications for our understanding of the relationship between English and European Protestant nations in the context of the Thirty Years' Wars. News from the military camp of the Lutheran King of Sweden offered a subtle way of promoting and normalising non-Calvinist forms of worship in England, and thus provides evidence that a range of Protestants were utilising the London news presses to advance their religious agenda in the early 1630s.